Compositional analysis on the reverted austenite and tempered martensite in a Ti-stabilized supermartensitic stainless steel: Segregation, partitioning and carbide precipitation. (15th February 2018) - Escobar, J.D.; Poplawsky, J.D.; Faria, G.A.; Rodriguez, J.; Oliveira, J.P.; Salvador, C.A.F.; Mei, P.R.; Babu, S.S.; Ramirez, A.J.
Abstract: Controlling the amount of reverted austenite at room temperature allows for tailoring of mechanical properties in supermartensitic stainless steels. The austenite reversion and stabilization occurs during inter-critical tempering through partitioning of austenite-stabilizing elements. The degree of partitioning greatly depends on the reversion temperature, which dictates the local equilibrium conditions. Atom probe tomography and energy dispersive spectroscopy in transmission electron microscopy were used to study the austenite reversion mechanism in terms of the elemental distribution of austenite-stabilizing, ferrite-stabilizing and carbide forming elements. Synchrotron X-ray diffraction confirmed that the austenite equilibrium phase fraction was reached after 2.5 h of isothermal reversion at 625 °C, allowing for direct comparison with thermodynamic and kinetic calculations. However, such soaking time was not enough to produce compositional homogenization in the reverted austenite. The austenite reversion and stabilization mechanism was related mainly to strong partitioning of Ni. Negligible partitioning of Cr, Mo, Si and Ti were observed. Instead, these elements were strongly segregated at the reverted austenite/martensite interfaces. Carbon and Ti played a secondary role in the austenite stabilization through the precipitation of nano-sized Ti (C, N) with partial substitution of Ti by Mo. Virtually carbon-free austenite and martensite were observed away from the interfaces and precipitates. Graphical abstract: Image 1 Highlights: Austenite growth occurred by strong partitioning of Ni according to local equilibrium. Reverted austenite/martensite interface segregation of Cr, Mo, Si and Ti was evidenced. Virtually carbon-free reverted austenite and martensite were found after tempering due to precipitation of Ti (C, N).